PENGARUH JENIS INDUSTRI, UKURAN PERUSAHAAN, PROFITABILITAS, DAN KEPEMILIKAN PEMERINTAH TERHADAP PENGUNGKAPAN EMISI GAS RUMAH KACA (Studi Empiris Pada Perusahaan Sektor Non Keuangan yang teratat di Bursa Efek Indonesia (BEI) 2015-2017) - Byantra Gunawan; Wahyu Meiranto (Diponegoro Journal of Accounting, 2020)
The study aims to determine the effect of industry type, company size, profitability and ownership on government disclosure of greenhouse gas emissions in non-financial companies listed on the Indonesia Stock Exchange (IDX).This research uses a quantitative method. The sample used in this study is a non-financial company listed on the Indonesia Stock Exchange in 2015 - 2017. The samples of this study used a purposive sampling method. The number of samples in this research is 19 companies.Data analysis uses multiple linear regression. The results of this analysis prove that the type of industry, company size, profitability does not affect the disclosure of greenhouse gases. However, government ownership has a significant effect on the disclosure of greenhouse gases.